The Promoting Role of Different Carbon Allotropes Cocatalysts for Semiconductors in Photocatalytic Energy Generation and Pollutants Degradation - Han, Weiwei; Li, Zhen; Li, Yang; Fan, Xiaobin; Zhang, Fengbao; Zhang, Guoliang; Peng, Wenchao (Frontiers in Chemistry, 2017)
Semiconductor based photocatalytic process is of great potential for solving the fossil fuels depletion and environmental pollution. Loading cocatalysts for the modification of semiconductors could increase the separation efficiency of the photogenerated hole-electron pairs, enhance the light absorption ability of semiconductors, and thus obtain new composite photocatalysts with high activities. Kinds of carbon allotropes, such as activated carbon, carbon nanotubes, graphene, and carbon quantum dots have been used as effective cocatalysts to enhance the photocatalytic activities of semiconductors, making them widely used for photocatalytic energy generation and pollutants degradation. This review focuses on the loading of different carbon allotropes as cocatalysts in photocatalysis, and summarizes the recent progress of carbon materials based photocatalysts, including their synthesis methods, the typical applications and the activity enhancement mechanism. Moreover, the cocatalytic effect among these carbon cocatalysts is also compared for different applications. We believe that our work can provide enriched information to harvest the excellent special properties of carbon materials as a platform to develop more efficient photocatalysts for solar energy utilization.